2015
DOI: 10.3390/resources4040871
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Energy Usage and Energy Efficiency Behavior in Low- and High-Income Households: The Case of Kitwe, Zambia

Abstract: Energy efficiency has been an important topic since the latter part of the last century. This is because adoption of energy efficiency measures has been acknowledged as one of the key methods of addressing the negative impact of climate change. In Zambia, however, the need to adopt energy efficiency measures has not just been driven by the imperative to mitigate the negative effects of climate change but also by a critical shortage of energy. This research looks at households' energy consumption behavior in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Hackett and Lutzenhiser [60] showed that energy consumption between different households differs greatly, not only because of the different design and technology available at their homes, but also because of social and demographic differences such as household size, age, income, nationality, and race, as well as differences in values, beliefs, habits, and norms. However, other studies, like Malama et al [61], did not find a link between household income and energy-efficiency variables and argued that low-income and high-income areas use the same low energy-efficiency initiatives, and that public bodies need to adjust the way they disseminate information to customers, from the traditional advertisement approach to social distribution. The instruments for overcoming climate change mitigation behavioral barriers are systematized in Table 4.…”
Section: Barriers Of Households Behavior Change In Climate Change Mit...mentioning
confidence: 96%
“…Hackett and Lutzenhiser [60] showed that energy consumption between different households differs greatly, not only because of the different design and technology available at their homes, but also because of social and demographic differences such as household size, age, income, nationality, and race, as well as differences in values, beliefs, habits, and norms. However, other studies, like Malama et al [61], did not find a link between household income and energy-efficiency variables and argued that low-income and high-income areas use the same low energy-efficiency initiatives, and that public bodies need to adjust the way they disseminate information to customers, from the traditional advertisement approach to social distribution. The instruments for overcoming climate change mitigation behavioral barriers are systematized in Table 4.…”
Section: Barriers Of Households Behavior Change In Climate Change Mit...mentioning
confidence: 96%
“…In particular, the relationship between income and energy consumption in the residential sector is also investigated [77,[118][119][120][121][122], with special concern for social housing occupants [123]. The income-energy use relationship is often examined along with other contextual factors, such as age and employment status, as is the case of the research of Godoy-Shimizu et al, who found that according to statistical analyses, high electricity use is significantly correlated with social class, large household size, unemployment, and middle age, while low electricity use is significantly correlated with single-person households, small homes, and retirement [124].…”
Section: Contextual and User Differences In Energy Savingsmentioning
confidence: 99%
“…It assists in perceiving novel business challenges and opportunities by utilizing data aggregation and data mining techniques. Descriptive analytics use-cases include energy consumption [22], urban designing [23], etc. Predictive analytics describes what will happen and why.…”
Section: Iot Data Analyticsmentioning
confidence: 99%